Water hyacinth leaf protein concentrate as partial replacement for soybean meal in Nile tilapia Oreochromis niloticus diets - Hontiveros, Gaily Jubie Sela (Miag-ao, Iloilo University of the Philippines Visayas, 2014)
The present study evaluated the potential of water hyacinth leaf protein concentrate (WHLPC) as a substitute for soybean meal in diets of Nlle tilapia Oreochromis niloticus. apparent dry matter dgestibility of WHLPC was determined by feeding Nile tilapia (46.17 +,6.34 g) a reference and a test diet (consisted of 70 parts reference diet and 30 parts test ingredient. Results showed that the apparent dry matter digestibility (ADMD) of WHLPC was high at 76.40 + 11.19%. Effects of increasing replacement of soybean meal with WHLPC on survival, growth performance, feed utilization, carcass composition, and nutrient and energy retention in O. niloticus were also determined. Soybean meal in ni Nile tilapia diets was replaced with WHLPC at 15, 30, and 45%. The diets were fed to O. niloticus fry (0.045 + 0.001 g) for 90 days. Results indicated that WHLPC could substitute soybean meal at 45% with no adverse effects on the survival, growth, and feed conversion ratio of Nile tilapia. In addition, final body protein, lipid, and energy retentin were not significantly different in all dietary treatments.
Thesis (M. S. Fisheries-Aquaculture) -- Miagao, Iloilo : U. P. Visayas, April 2014.